Single-session interventions for adolescent anxiety and depression symptoms in Kenya: A cluster-randomized controlled trial. (April 2022) - Venturo-Conerly, Katherine E.; Osborn, Tom L.; Alemu, Rediet; Roe, Elizabeth; Rodriguez, Micaela; Gan, Jenny; Arango, Susana; Wasil, Akash; Wasanga, Christine; Weisz, John R.
Abstract: Objective: Expanding mental healthcare for adolescents in low-income regions is a global health priority. Group interventions delivered by lay-providers may expand treatment options. Brief, positively-focused interventions conveying core concepts of adaptive functioning may help reduce adolescent symptoms of mental illness. In this trial, we tested three such interventions (growth mindset, gratitude, and value affirmation) as separate single-session interventions. Method: Consenting adolescents (N = 895; Mage  = 16.00) from two secondary schools in Kenya were randomized by classroom (24 classrooms; Mclass  = 37.29 students) into single-session interventions: growth (N = 240), gratitude (N = 221), values (N = 244), or an active study-skills control (N = 190). Mixed-effects models controlling for age and gender were used to estimate individual-level intervention effects on anxiety and depression symptoms. Results: Within the universal sample, the values intervention produced greater reductions in anxiety symptoms than the study-skills control (p < .05; d = 0.31 [0.13-0.50]). Within the clinical sub-sample (N = 299), the values (p < .01; d = 0.49 [0.09-0.89]) and growth interventions (p < .05; d = 0.39 [0.01-0.76]) produced greater reductions in anxiety symptoms. There were no significant effects on depression. Conclusions: The values intervention reduced anxiety for the full sample, as did the growth mindset and values interventions for symptomatic youths. Future efforts should examine durability of these effects over time. Highlights: We test in a cluster RCT three single-session, lay-provider-delivered interventions. Single-session values and growth interventions both reduced anxiety symptoms. The single-session gratitude intervention did not reduce symptoms. No single-session intervention significantly reduced depression symptoms. The values intervention might be prioritized over the others for dissemination.